Teacher Selection in Finland - Ramin Izadi (Helsinki Graduate School of Economics, 2024)
Finland's success in international student comparisons is often attributed to the quality of its teachers. In this paper I examine the teacher selection process in Finland and highlight three key new findings. First, using rich administrative data for graduating cohorts between 1973-2012, I show that teacher graduates have consistently lower standardized test performance in comparison to other university graduates. However, in contrast to findings from other developed countries, they have been closing that gap during the last 40 years. Second, past test performance is a poor predictor of teacher aptitude, as measured by expert evaluators during entrance interviews for teacher training programs. This implies that the performance gap between teaching and other programs is not due to lack in applicant quality, but due to uncorrelated factors that influence the aptitude test performance in teaching. In other words, teacher training programs in Finland are not looking to enroll the academically best students. Third, relative to other university graduates with similar academic track record, teachers have high wages but low earnings, which helps to explain the popularity of teacher training programs in certain demographics.
Keywords: I21; J24; J31; 330; teacher skills; teacher compensation; occupational choice; education